Types of Waqf from the Perspective of Fiqh and Regulation in Indonesia - Istiyah, Istiyah; Zafira, Nazwa Nadyan; Hartati, Sawitri Yuli (Edusight International Journal of Multidisciplinary Studies, 2025)
This study examines the various forms of waqf from the perspective of Islamic jurisprudence and Indonesian legislation. The research stems from the general understanding that waqf only involves immovable assets such as land and buildings. The purpose of this study is to analyze the expansion of waqf objects to include movable assets such as cash, precious metals, securities, vehicles, and intellectual property rights, and to review their validity according to the Four Madhhabs and Indonesian law. The research employs a qualitative library method, analyzing primary sources such as legislation and fiqh books, and secondary sources from academic journals and literature. The results indicate that most of the Four Madhhabs, Hanafi, Maliki, Shafi’i, and Hanbali, permit movable waqf as long as it provides lasting benefits and complies with sharia principles. The study concludes that the legal framework established through Law Number 41 of 2004 and its implementing regulations strengthens waqf as a productive economic instrument for community welfare and sustainable development